Mozambique : Sixth Review Under the Policy Support Instrument, Second Review Under the Arrangement Under the Exogenous Shocks Facility, and Request for a Three-Year Policy Support Instrument; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mozambique. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Mozambique showed considerable resilience to the global crisis. The government responded to the crisis by promptly easing macroeconomic policies. The Policy Support Instrument (PSI) provided an effective and flexible framework to guide policies during the crisis, and program performance has been strong. Donor support was temporarily halted over governance concerns, but has resumed. Mozambique's economic performance and track record of macroeconomic stability over the last decade and a half have been impressive, making the country a prime example of a mature stabilizer.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet